PENGEMBANGAN KOMPETENSI KEPROFESIAN BERKELANJUTAN PENDIDIK ANAK USIA DINI DI KECAMATAN JATEN KABUPATEN KARANGANYAR - Nanik Dwi Nurhayati; Budi Hastuti (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2017)
The aim research to determine the level of professions competence and efforts development professions competence to early childhood theacher in Jaten Karanganyar. The Research is descriptive quantitative research with competence theacher variable. Respondents are early childhood theacher who are in group Himpaudi Jaten. The technique of collecting data through interviews, observations, questionnaires closed and open. The validity of the data using content validity. Data were analyzed using a formula to determine the percentage of achievement of each component. The results showed competence level of profession of early childhood theacher in Jaten aspects of profession competency subject matter and methods of 84,6% category very well, the aspect of profession competency curriculum and syllabus of 88,3% category very well, the aspect competence development profession ethics of 74,7% category excellent and efforts most effectively professional competence development through the training. The theacher have conducted of subject matter and methods appropriate 13th curriculum and syllabus, develop ethical scientific excellent professionalism. Nevertheles need to improve of the classroom action research and making scientific that do rarely to theacher to improve professionalism competence.